Cardiac Stim1 Silencing Impairs Adaptive Hypertrophy and Promotes Heart Failure Through Inactivation of mTORC2/Akt Signaling. Issue 15 (12th April 2016) - Bénard, Ludovic; Oh, Jae Gyun; Cacheux, Marine; Lee, Ahyoung; Nonnenmacher, Mathieu; Matasic, Daniel S.; Kohlbrenner, Erik; Kho, Changwon; Pavoine, Catherine; Hajjar, Roger J.; Hulot, Jean-Sébastien
Abstract : Background—: Stromal interaction molecule 1 (STIM1) is a dynamic calcium signal transducer implicated in hypertrophic growth of cardiomyocytes. STIM1 is thought to act as an initiator of cardiac hypertrophic response at the level of the sarcolemma, but the pathways underpinning this effect have not been examined. Methods and Results—: To determine the mechanistic role of STIM1 in cardiac hypertrophy and during the transition to heart failure, we manipulated STIM1 expression in mice cardiomyocytes by using in vivo gene delivery of specific short hairpin RNAs. In 3 different models, we found that Stim1 silencing prevents the development of pressure overload–induced hypertrophy but also reverses preestablished cardiac hypertrophy. Reduction in STIM1 expression promoted a rapid transition to heart failure. We further showed that Stim1 silencing resulted in enhanced activity of the antihypertrophic and proapoptotic GSK-3β molecule. Pharmacological inhibition of glycogen synthase kinase-3 was sufficient to reverse the cardiac phenotype observed after Stim1 silencing. At the level of ventricular myocytes, Stim1 silencing or inhibition abrogated the capacity for phosphorylation of Akt S473, a hydrophobic motif of Akt that is directly phosphorylated by mTOR complex 2. We found that Stim1 silencing directly impaired mTOR complex 2 kinase activity, which was supported by a direct interaction between STIM1 and Rictor, a specific component of mTOR complex 2. Conclusions—: These data support a model whereby STIM1 is critical to deactivate a key negative regulator of cardiac hypertrophy. In cardiomyocytes, STIM1 acts by tuning Akt kinase activity through activation of mTOR complex 2, which further results in repression of GSK-3β activity. Abstract : Supplemental Digital Content is available in the text.